CXCL12/SDF-1 in IgG4-Related Disease - Capecchi, Riccardo; Croia, Cristina; Puxeddu, Ilaria; Pratesi, Federico; Cacciato, Andrea; Campani, Daniela; Boggi, Ugo; Morelli, Luca; Tavoni, Antonio; Migliorini, Paola (Frontiers in Pharmacology, 2021)
BACKGROUND: CXCL12/SDF-1 is a chemokine with pleiotropic functions in hematopoietic stem cells niche homeostasis, germinal centre architecture, B cells maturation, neoangiogenesis and fibrosis. Recently, the CXCL12/CXCR4/CXCR7 axis was associated to cancer metastasis and autoimmune diseases. IgG4-Related Disease (IgG4-RD) is a pathological condition characterized by IgG4+ plasma cells infiltrating fibrotic lesions. Aim of this research was to investigate the relevance of SDF-1/CXCL12 in IgG4-RD. MATERIALS AND METHODS: Peripheral blood samples were collected before therapy from a single centre cohort of 28 IgG4-RD patients, fulfilling the ACR-EULAR classification criteria. Clinical and serological data were obtained for each patient. Fourteen healthy donors (NHS), 9 patients with pancreatic ductal adenocarcinoma (PDAC) and 9 with Sjogren Syndrome (SSj) were recruited as controls and screened for circulating SDF-1/CXCL12 by ELISA. Moreover paraffin-embedded pancreatic biopsies obtained from patients with IgG4-RD (n=7), not-autoimmune pancreatitis (n=3), PDAC (n=5) and from control tissues (n=4) were analysed to study the tissue expression and localization of SDF-1/CXCL12 and one of its receptor CXCR4, and their potential relation with neutrophil extracellular traps (NETs). RESULTS: IgG4-RD patients had higher serum levels of SDF-1/CXCL12 than normal controls (p=0,0137). Cytokine levels did not differ between IgG4-RD autoimmune pancreatitis (AIP) and retroperitoneal fibrosis, nor between single- and multiple-organs involvement. No correlation was seen with IgG4-RD Responder Index, IgG4 levels, white blood cells or inflammatory markers in the serum. When compared to SSj, IgG4-RD AIP subgroup presents higher amounts of serum SDF-1/CXCL12 (p=0,0275), while no differences are seen in comparison with PDAC. The expression of SDF-1/CXCL12 in the tissue was significantly higher in IgG4-RD tissue than normal pancreas and the tissue with high SDF-1/CXCL12 expression is characterized by the overall inflammatory cell infiltration, fibrosis and high level of NETs. CONCLUSION: Modulating B cell development, neoangiogenesis and fibrosis, SDF-1/CXCL12 may play a role in IgG4-RD. The higher levels observed in IgG4-RD as compared to SSj, that closely mimics the disease, can be related to a different pattern of lesions, with a prevalent fibrosis seen in IgG4-RD. Taken together, these findings suggest that drugs acting on the CXCL12/CXCR4/CXCR7 axis may affect IgG4-RD